SURGICAL MANAGEMENT OF PERSISTENT RIGHT AORTIC ARCH IN A GERMAN SHEPHERD DOG – A CASE REPORT - P. Sankar; D. Mouri Javagar; M. Bharathidasan; Mohamed Shafiuzama; Ravi Sundar George (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A 2 month old male German shepherd dog was presented to Veterinary Clinical Complex, Small Animal Surgery Unit of Madras Veterinary College, Chennai with the history of persistent regurgitation for 15 days. Plain and positive contrast radiographic evaluation revealed the dilated oesophagus cranial to the heart and tracheal deviation with constriction at the base of the heart. Surgical correction through resection of persistent ligamentum arteriosum around the oesophagus under general anaesthetic procedure. Post operative plain and contrast radiographic procedure revealed no evidence of barium stasis in the course of oesophagus and complete resolution of regurgitation. Recovery was good and normal feeding habit noticed 14th post operative day.